2019
DOI: 10.1016/j.jpsychores.2019.05.001
|View full text |Cite
|
Sign up to set email alerts
|

The effects of cognitive behavioral and mindfulness-based therapies on psychological distress in patients with multiple sclerosis, Parkinson's disease and Huntington's disease: Two meta-analyses

Abstract: Psychological distress has a high impact on quality of life in patients with multiple sclerosis (MS), Parkinson's disease (PD), and Huntington's disease (HD). Studies have shown that cognitive behavioral therapy (CBT) and mindfulness-based therapies (MBTs) are successful in reducing psychological distress in patients with anxiety, depressive, and chronic somatic disorders. We aimed to investigate the effectiveness of these therapies in MS, PD, and HD patients. Methods: We performed a comprehensive literature s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 55 publications
1
32
0
2
Order By: Relevance
“…A recent meta-analysis showed that cognitive behavioural therapy and mindfulness-based therapies are successful in reducing psychological distress in patients with MS, but effects are small to moderate; more high-quality treatment studies are warranted. 51 Some limitations of our study need to be mentioned. First, our study has a cross-sectional design, so we cannot draw conclusions about the direction of the effects.…”
Section: Ta B L E 2 Means and Standard Deviations Of Psychological Qumentioning
confidence: 96%
See 1 more Smart Citation
“…A recent meta-analysis showed that cognitive behavioural therapy and mindfulness-based therapies are successful in reducing psychological distress in patients with MS, but effects are small to moderate; more high-quality treatment studies are warranted. 51 Some limitations of our study need to be mentioned. First, our study has a cross-sectional design, so we cannot draw conclusions about the direction of the effects.…”
Section: Ta B L E 2 Means and Standard Deviations Of Psychological Qumentioning
confidence: 96%
“…We suggest it is not the disease-specific factors that contribute to anxiety, but how well patients adjust to the disease. A recent meta-analysis showed that cognitive behavioural therapy and mindfulness-based therapies are successful in reducing psychological distress in patients with MS, but effects are small to moderate; more high-quality treatment studies are warranted 51. More specifically, a greater reliance on emotion-focused coping strategies is related to poor psychosocial adjustment, depression and anxiety 49.…”
mentioning
confidence: 99%
“…Parkinsonism is one of the most common neurodegenerative disorders with motor and nonmotor symptoms (Ghielen et al, 2019). Stem cell‐based treatments are considered as the most promising approach that could be widely used in a large number of patients (Palmer, Coronel, Bernabeu‐Zornoza, & Liste, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Areas not yet addressed in the literature Despite extensive evidence showing that obsessive-compulsive symptoms and perseverative behaviours are highly prevalent among premanifest and especially symptomatic pwHD [21,24], no psychological interventions have been carried out so far to address them specifically. However, based on a rich literature highlighting that both face to face and telephone-delivered CBT are effective at reducing obsessive-compulsive symptoms and perseverative behaviours in the general population [92,93]-as well as that they are feasible with other motor neurodegenerative diseases like multiple sclerosis and Parkinson's disease [94,95]-the adoption of such approach for premanifest and early-stage pwHD should be explored by future studies.…”
Section: Copingmentioning
confidence: 99%